The float test : a novel - Strong, Lynn Steger, 1983- (Mariner Books, 2025)
"The Kenner siblings are at odds. Jenn is a harried mom struggling under the weight of family obligations. Fred is a novelist who can't write, maybe because she's lost faith in storytelling itself. Jude is a recovering corporate lawyer with her own story to tell, and a grudge against her former favorite sister, Fred. George, the baby, is estranged from his wife and harboring both a secret about his former employer and an ill-advised crush on one of his sisters' friends. Gathered after a major loss, each sibling needs the others more than ever--if only they could trust each other. A family story is, of course, only as honest as the person telling it. This family story in particular is fraught with secrets about kids and sex and jobs and why the Kenner matriarch had a gun in her underwear drawer. The biggest secret of all though is the secret of what happened between Jude and Fred to create such a rift between the two once-close middle sisters. Over the course of a sweltering Florida summer, the Kenner siblings will revisit what it means to be a family and, if they are smart and kind and lucky, come out on the other side better for having each other. A rich exploration of family, ambition, secrets, and love, The Float Test is an elegant and gripping testament to the power that family has to both nurture and destroy us from a critically acclaimed writer working at the top of her craft"--